Characterization of Luteal Response to PGF2α Treatment During Mid-luteal Phase in Graded Murrah Buffaloes - Thulasiraman, Sarath; Annadurai, Thangamani; Ramasamy, Rajkumar; Abdul, Reshma; Manokaran, Sakthivel (The Indian Journal of Animal Reproduction, 2025)
The present study was conducted with the objective to evaluate the functional and structural regression of corpus luteum following administration of PGF2 α during mid-luteal phase of estrous cycle in graded Murrah buffaloes. Healthy, plu riparous lactating and cyclic graded Murrah buffaloes (n=7; 6-8 years) were administered with PGF2 alpha (Cloprostenol sodium, 500µg) intramuscularly during mid-luteal phase of estrous cycle and recorded luteolysis (functional, structural regression) and corresponding follicular growth periodically from time of administration (0, 6, 12, 24, 48hr and 72 hr). Results showed that the significant decrease in size of CL at 24, 48hr and 72 hr, while progesterone concentration reached to its basal level (
Keywords: Corpus luteum; Buffalo; Luteolysis; Progesterone; PGF2α